contestada

Given that the first term is: T1 = 2, and the recursive definition is: t n + 1 = 3 ( t n ), what would be the 2nd term

Group of answer choices

3

9

27

81

Respuesta :

Answer:

The second term of the sequence is T(2)  = 6.

Step-by-step explanation:

Here, the first term is given as

T(1)  = 2

The general Formula for nth term is given as:

T(n  + 1) =  3(T(n))

Now, here the second  term

for,  n = 1

T(1+1) = 3 (T(1))

or, T(2)  = 3 T(1)

⇒ T(2)  = 3 x 2 = 6

Hence, the second term of the sequence is T(2)  = 6.

Answer: 9

Step-by-step explanation: i got a 100